Cytomorphometric analysis of buccal mucosal cells in iron deficiency anemia: A cross-sectional study - S Patil Swati; J Palaskar Sangeeta; R Narang Bindiya; B Pawar Rasika; T Kathuriya Pargatsingh; S Khandalkar Yogesh (Indian Journal of Pathology and Microbiology)
Background: Worldwide, at any given moment, more individuals have iron deficiency anemia (IDA) than any other health problems. Very few studies have been conducted to evaluate changes in oral mucosa in IDA. The present study is undertaken for cytomorphometric analysis of buccal mucosal cells in IDA. Nuclear diameter (ND), cell diameter (CD), nuclear area (NA), cell area (CA), and nuclear-cytoplasmic ratio (N/C) are measured and compared in buccal mucosal cells of IDA patients and controls. Aims: To evaluate cytomorphometric changes in epithelial cells of oral mucosa in IDA and to compare these changes with the controls. Settings and Design: A cross-sectional study. Methods and Materials: Forty cases of IDA and forty cases of control group were selected for the study. IDA cases were diagnosed with decreased Hb level, MCV, MCH, MCHC and confirmed by decreased serum iron and increased total iron-binding capacity levels. Cytomorphometric analysis of buccal mucosa was performed to study CA, CD, NA, ND, and N/C ratio. Statistical Analysis Used: Statistical analysis was done using t- test in SPSS software version 4. Result: Results of our study showed increased cell area, cell diameter, nuclear area, nuclear diameter, and nuclear-cytoplasmic ratio in anemic group as compared to controls. Conclusion: The study suggests that individuals with IDA regardless of clinically visible oral lesions show cytological changes in oral mucosal epithelium. Knowledge of quantitative alterations in oral epithelial cells of IDA patients is important as these alterations are similar to those seen in precancerous and radiation-induced changes. Cytomorphometry is an efficient tool to understand the extent of cellular changes that occur in oral epithelial cells in IDA.